Debt-Based Versus Equity-Based Financing: A Comparative Analysis on Efficiency of Islamic Financial System - Abdullateef Abdulqadir Maikabara; Sri Maulida; Abdulmajeed M Aderemi (Universitas Ahmad Dahlan, 2020)
Introduction to The Problem: The financial system, as a subset of economics, plays a prominent role in solidifying the socio-economic development and wellbeing of people of a society. However, debt-based and equity-based financing are the main models employed by Islamic financial institutions to help small and medium enterprises (SMEs) that need funding to facilitate their businesses' projects. Operationally, debt-based financing seems to be the prominent financing model than equity-based financing, which only accounts for either zero or small scale in Islamic financial institutions.Objective Study: This study explores the rightful financing model that can contribute much better to the efficiency of the Islamic financial system in achieving socio-economic development.Methodology: To achieve the study's purpose, a literature-based method and secondary data collection technique are adopted as related previous studies from articles, books, conferences, and working papers are reviewed and analyzed.Findings: Equity-based model as a partnership model is somewhat more productive in contributing to socio-economic development than debt-based financing, but not being widely applied due to specific issues such as high risk, agency problem, costumer’s awareness, and sensitivity, and others more. It is recommended that researchers empirically investigate the suitable financing model between debt-based and equity-based financing models to ensure the achievement of sustainable socio-economic development.